Folk media: Existence, forms, uses and challenges in Mende indigenous communities of Southern Sierra Leone - Thulla, Foday Yamba Philip; Koroma, Ayuba; Moriba, Samba; Fofanah, Ibrahim Mustapha (Research Journal in Advanced Humanities, 2022)
The study examined the folk media: existence, forms, uses and challenges in the Mende indigenous communities of Southern Sierra Leone. A mixed methods research design of 120 participants was developed, selected from 3 communities with 40 participants in each community. The mixed approach used both quantitative and qualitative research designs in the study. The interviews were initially conducted using interview questions related to the existence of folk media, its use and the challenges it faced in the study area. Three focus group discussions were held in 3 communities, randomly selected on the outskirts of the Southern part of Sierra Leone. A quantitative research approach helped analyse simple statistical data collected by the researchers. The findings revealed that folk media exist in the Mende communities studied; and that the use of Mende folk media is fraught with major challenges. The findings also revealed that the use of Mende folk media is rare in indigenous Mende communities which is a major challenge in preserving the practices and their uses in the selected communities. The findings also showed that Mende folk media play an important role in disseminating social, religious, and cultural information, including being used in ceremonies such, as litigation, court hearings, singing and storytelling sessions, naming, weddings and political campaigns, and funerals. The findings also revealed that traditional Mende media are mainly used by the nominees of Paramount Chiefs, the community griots, the heads of the tribal and secret societies and volunteers.